2019
DOI: 10.9734/ijpss/2019/v27i230072
|View full text |Cite
|
Sign up to set email alerts
|

Soybean (Glycine max L.) Response to Lime and Vermicompost Amelioration of Acidic Nitisols of Assosa, North Western Ethiopia

Abstract: Acidic soils limit the production potential of crops because of low availability of basic cations and excess of hydrogen (H+) and aluminium (Al3+) in exchangeable forms. In the western part of the country such as Assosa and Wellega, soil acidity is a well-known problem limiting crop productivity. A field study was conducted to assess the effects of lime, vermicompost and their combinations on selected soil physico-chemical properties and responses of soybean grown on acidic Nitisols of Assosa area during 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…This might be due to combined application of lime with vermicompost, which resulted in improved soil conditions, such as soil pH, increased soil OM and reduction of exchangeable acidity. This result was supported by the finding of [48] who reported increment of soil CEC when lime and vermicompost amendments applied to acid soil. Cation exchange capacity of the soil was not significantly increased by the combined application of lime and VC.…”
Section: Exchangeable Bases Cation Exchangeable Capacity and Base Sat...supporting
confidence: 79%
See 2 more Smart Citations
“…This might be due to combined application of lime with vermicompost, which resulted in improved soil conditions, such as soil pH, increased soil OM and reduction of exchangeable acidity. This result was supported by the finding of [48] who reported increment of soil CEC when lime and vermicompost amendments applied to acid soil. Cation exchange capacity of the soil was not significantly increased by the combined application of lime and VC.…”
Section: Exchangeable Bases Cation Exchangeable Capacity and Base Sat...supporting
confidence: 79%
“…Adsorption of organic anions on hydrous Fe and Al surfaces and the corresponding release of hydroxyl ions increased soil pH and reduced exchangeable acidity [44]. [48] also reported that addition of organic manures to acid soils increased soil pH, decreased Al saturation, and thereby improved soil conditions for plant growth. The lowest exchangeable acidity values were recorded for combined application of lime at 75% LR + 2.5 t VC ha -1 (0.31 cmol c kg -1 ) followed by 100% LR + 5 t VC ha -1 (0.33 cmol c kg -1 ) and 100% LR + 2.5 t VC ha -1 (0.35 cmol c kg -1 ) while the highest was recorded for the control (2.44 cmol c kg -1 ) (Table 6).…”
Section: Soil Ph and Exchangeable Aciditymentioning
confidence: 91%
See 1 more Smart Citation
“…The possible reason for the greater number of nodules developed on the root of soybean after vermicompost application and NPS fertilization might be the importance P and S elements that found in NPS used in enhancing nodulation, symbiotic association between rhizobia and host plant and consequently improved N2 fixation. Likewise, application of vermicompost supply necessary nutrients (N, P, S, K and Fe) important for nodules formation and Rhizobia bacteria are sensitive to soil acidity and require P, adequate soil moisture for their multiplication [41,42]. In agreement with this result application of 16 t FYM ha -1 + 60 kg S ha -1 on soybean-wheat cropping system produced maximum mean number of nodules per 5 plant (231) across 3 years [43].…”
Section: Nodulation and Growth Parametersmentioning
confidence: 56%
“…The possible reason of high number of effective nodules with vermicompost application might be due to the availability of calcium might enhance root development and root nodulation [51,52]. This might be due to combination of organic and inorganic nutrition provides better soil environment for root growth, nodule formation, availability and absorption of nutrient from soil [46,42]. Similarly application of 16 t FYM ha -1 + 60 kg S ha -1 on soybeanwheat cropping system produced maximum mean number of effective nodules per 5 plants (325) across 3 years, [43].…”
Section: Nodulation and Growth Parametersmentioning
confidence: 99%